The Role of NGOs in Environmental Governance in Indonesia: Peran Ornop dalam Tata Kelola Lingkungan Hidup di Indonesia - Sorik, Sutan; Nurhidayah, Laely (Jurnal Konstitusi, 2024)
The role of non-governmental organizations (NGOs) needs to be strengthened to enhance the capacity for environmental governance in Indonesia, as natural resources cannot be effectively protected, and environmental problems cannot be resolved without collaboration between the government and civil society. This research aims to explain the concept and role of NGOs as actors in environmental governance. The research was conducted through a literature review. The results show that NGOs play a significant role in protecting natural resources and assisting in solving environmental issues. In Indonesia, the role of NGOs has been legally strengthened. However, due to the restrictive nature of the environmental legal system, not all NGOs have legal standing to bring lawsuits before the courts. To preserve the environment, the legal standing of NGOs should not be limited, as environmental lawsuits involve the broader public interest and the sustainability of natural resources, both of which must be safeguarded.